PENGARUH PEMBELAJARAN BERBASIS EDMODO TERHADAP MOTIVASI BELAJAR MAHASISWA PGSD STKIP MUHAMMADIYAH MUARA BUNGO - andam yulianti; Puput Wahyu Hidayat (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The background in this study is the learning motivation of STKIP Muhammadiyah Muara Bungo students is still low in Indonesian subjects. One reason is the learning approach that is not right. Although the implementation has implemented learning by leading students to be more active in learning, but there are still weaknesses in learning, which causes low motivation to learn. This can be seen when doing learning activities, students prefer to chat with their friends when friends in the group in front are explaining the material. Another thing that happens is, when students do not master the group material, the audience becomes noisy, so that learning time is wasted. So, with existing problems, an effort can be made to improve learning activities. One effort that can be done is by applying edmodo-based learning. The purpose of this study was to determine the effect of Edmodo-based e-learning learning approaches on the learning motivation of STKIP Muhammadiyah Students in Muara Bungo. This type of research is a quasi-experimental study with pretest-posttest nonequivalent group design. This research has been carried out in STKIP Muhammadiyah Muara Bungo PGSD Study Program in 2020. The instrument used to measure learning motivation was 30 statements. Data were analyzed using descriptive analysis test and inferential analysis test which included tests of normality, homogeneity and hypothesis testing. The results showed that there was a significant influence with edmodo-based e-learning learning on student motivation.